Photocatalytic chloride-to-chlorine conversion by ionic iron in aqueous aerosols: a combined experimental, quantum chemical, and chemical equilibrium model study - M. K. Mikkelsen; J. B. Liisberg; M. M. J. W. van Herpen; K. V. Mikkelsen; M. S. Johnson (Aerosol Research)
Prior aerosol chamber experiments show that the ligand-to-metal charge transfer absorption in iron(III) chlorides can lead to the production of chlorine (Cl2/Cl). Based on this mechanism, the photocatalytic oxidation of chloride (Cl−) in mineral dust–sea spray aerosols was recently shown to be the largest source of chlorine over the North Atlantic. However, there has not been a detailed analysis of the mechanism that includes the aqueous formation equilibria and the absorption spectra of the iron chlorides nor has there been an analysis of which iron chloride is the main chromophore. Here we present the results of experiments measuring the photolysis of FeCl3 ⋅ 6H2O in specific wavelength bands, an analysis of the absorption spectra of FeCl<msubsup>n3-n</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="17pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="fb86d1cea1d2072e93be953ab610af6f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ar-2-31-2024-ie00001.svg" width="17pt" height="16pt" src="ar-2-31-2024-ie00001.png"/></svg:svg> (n=1 … 4) made using density functional theory, and the results of an aqueous-phase model that predicts the abundance of the iron chlorides with changes in pH and iron concentrations. Transition state analysis is used to determine the energy thresholds of the dissociations of the species. Based on a speciation model with conditions extending from dilute water droplets and acidic seawater droplets to brine and salty crust, as well as the absorption rates and dissociation thresholds, we find that FeCl<msubsup>2+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="a685953c08dd2ff7fc811710de5bbda3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ar-2-31-2024-ie00002.svg" width="8pt" height="15pt" src="ar-2-31-2024-ie00002.png"/></svg:svg> is the most important species for chlorine production for a wide range of conditions. The mechanism was found to be active in the range of 400 to 530 nm, with a maximum around 440 nm. We conclude that iron chlorides will form in atmospheric aerosols from the combination of iron(III) cations with chloride and that they will be activated by sunlight, generating chlorine (Cl2/Cl) from chloride (Cl−) in a process that is catalytic in both chlorine and iron.